Angiomyolipoma in the Temporal Region: A Case Report - Calenthia Ekawati; Nico Lumintang; Sherly Tandililing (Universitas Sam Ratulangi, 2024)
Abstract: Angiomyolipomas are benign tumors (consisting of fat tissues, smooth muscles, and blood vessels) that are often found in the kidney or liver. However, they are rarely found in the head and neck region and require proper management. We reported a 13-year-old girl presented with a mass in the right temple since last year. Musculoskeletal ultrasound (US) and contrast-enhanced computed tomography (CT) scan showed a well-defined hypoechoic lesion in the right temporal subfascial region, with a suspicion of a hemangioma. The patient underwent resection of the lesion. The diagnosis of angiomyolipoma was confirmed through a histopathological examination. The patient was subsequently discharged on the third postoperative day and had no further treatment. In conclusion, extraperitoneal angiomyolipomas are rarely found, and the diagnosis is confirmed by histopathological examination. The management of temporal angiomyolipomas is tumor resection. Keywords: temporal angiomyolipomas; histopathological diagnosis; surgical treatment